2016
DOI: 10.7205/milmed-d-15-00241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Resuscitative Methods for Venlafaxine Toxicity in a Swine Model

Abstract: The results suggest that in swine models, the optimal treatment for venlafaxine overdose would include vasopressin with lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A literature review reported an acute toxic dose of 1,500 to 7,500 mg (10 mg/kg in humans). 10 Other studies 19 used intravenous injections of acute toxic doses of 40 to 50 mg/kg in pigs. This dose is similar to the LD 50 of female rats (350 mg/ kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review reported an acute toxic dose of 1,500 to 7,500 mg (10 mg/kg in humans). 10 Other studies 19 used intravenous injections of acute toxic doses of 40 to 50 mg/kg in pigs. This dose is similar to the LD 50 of female rats (350 mg/ kg).…”
Section: Discussionmentioning
confidence: 99%
“…18 However, only a small number of controlled studies have detailed poisoning with this drug. 19 Although VEN exerts wellknown toxic effects on the nervous and cardiovascular systems, the potential toxic effects of this drug on other major organ systems must be investigated. Therefore, the aim of this study is to investigate acute and subchronic toxicity of VEN in liver, kidney, and gastric tissues.…”
Section: Introductionmentioning
confidence: 99%